Understanding Gastritis: Causes, Symptoms, Diagnosis, and Management - Akram, Muhammad; Mahmood, Abid; Umaru, Isaac John; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammad (Darul Yasin Al Sys, 2025)
One such common disorder is gastritis, that is bound to cause acute or chronic inflammation of the stomach lining. It is primarily caused due to the long duration use of NSAIDs, Helicobacter pylori infection or many other reasons. Alcohol consumption, stress, bile reflux and some immunological processes also play a role in causing gastritis. While some relatives remain asymptomatic, most relatives experience symptoms such as epigastric discomfort, vomiting, and, in some cases, gastrointestinal bleeding. H. Pylori detection, endoscopic examination, and histopathology are the primary techniques for diagnosing gastritis. Another method of treatment is the use of proton pump inhibitors along with lifestyle changes, or antibiotics. Gastritis and its symptoms can be mitigated by employing primary prevention strategies like proactively treating H. Pylori infections or reducing NSAIDs consumption.